(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1993)
The definition of a regional guide-level, named Faraoni Level, in the Maiolica limestone of the Umbria-Marche Apennines is proposed in this paper. The age of the Faraoni Level is latest Hauterivian. Abundant ammonites date it as angulicostata zone, catulloi subzone. The level is characterized by the alternation of white micritic limestones and black shales with high organic marrer conrent.